An Improved Finite-Set Predictive Control for Permanent Magnet Synchronous Motors Based on a Neutral-Point-Clamped Three-Level Inverter - Guozheng Zhang; Jiangyi Zhao; Yufei Liu; Xin Gu; Chen Li; Wei Chen (World Electric Vehicle Journal)
Numerous voltage vectors exist in a neutral-point-clamped (NPC) three-level inverter. Traditional three-level model predictive control incurs a heavy online computational burden. This paper proposes a model predictive torque control strategy for NPC three-level inverters with permanent magnet synchronous motor systems. First, the relationship among the stator flux linkage vector position, the torque–flux linkage increment, and the stator flux linkage variation is analyzed. Then, the candidate voltage vector sector is determined, and the candidate voltage vectors are selected from it. Meanwhile, the direction of the load current flowing to the neutral point and the voltage difference between the upper and lower capacitors are evaluated. As a result, redundant small vectors are effectively selected, reducing the number of candidate voltage vectors to six and avoiding the computation of all possible vectors. The experimental results from an NPC three-level inverter–permanent magnet synchronous motor system verify that this strategy significantly reduces the computational complexity and provides excellent dynamic and steady-state performance.